LEMBAGA PASCA-KONFLIK DAN PROSES PERDAMAIAN DI FILIPINA SELATAN - Trijono, Lambang (JURNAL ILMU BUDAYA, 2014)
This writing is an attempt to understand the roles of post conflict insititution and the peaceprocess in Southern Philippines. Strengthening post conflict institution that was the outcome ofprevious peace agreement is crucial to push for integration and further peace process. Thedynamics between conflict and peace in Mindanao show the close connectin between coflict andpeace process. When peace process gathered its peace, conflict subsided. And in contrary, whenpeace process stalled, conflict emerged and violence tookplace which threatened human security.This writing deals with four aspects. One, a review of corrent conflict and peace process inMindanao. Second, the weakening of the peace process and the rising threat to human security.Third, humanitarian efforts thus far conducted and lessons learned of such efforts. And finally,this paper will see the conncetion between conflict and peace process in Mindanao and theSabah-Sulu incident. Based on the discussions, this paper will suggest a recommendation to pushforward the peace process and the resolve the Sabah-Sulu problem on ASEAN Comunity level.Keywords: Post-conflict institutions, Peace process, Souther Philippines, Human security